Anesthesia and Sedation Practices Among Neurointerventionalists during Acute Ischemic Stroke Endovascular Therapy - McDonagh, David L.; Olson, DaiWai M.; Kalia, Junaid S.; Gupta, Rishi; Abou-Chebl, Alex; Zaidat, Osama O. (Frontiers in Neurology, 2010)
Background and Purpose: Intra-arterial reperfusion therapies are expanding frontiers in acute ischemic stroke (AIS) management but there is considerable variability in clinical practice. The use of general anesthesia (GA) is one example. We aimed to better understand sedation practices in AIS. Methods: An online survey was distributed to the 68 active members of the Society of Vascular and Interventional Neurology (SVIN). Survey development was based on discussions at the SVIN Endovascular Stroke Round Table Meeting (Chicago, IL, 2008). The final survey contained 12 questions. Questions were developed as single and multiple-item responses; with an option for a free-text response. Results: There was a 72% survey response rate (N=49/68). Respondents were interventional neurologists in practice 1-5 years (71.4%, N=35). The mean (± SD) AIS interventions performed per year at the respondents' institutions was 42.5 ± 25, median 35.0 (IQR 20, 60). The most frequent anesthesia type used was GA (anesthesia team), then conscious sedation (nurse administered), monitored anesthesia care (anesthesia team), and finally local analgesia alone. There was a preference for GA because of eliminating movement (65.3% of respondents; N=32/49), perceived procedural safety (59.2%, N=29/49), and improved procedural efficacy (42.9%, N=21/49). However, cited limitations to GA included risk of time delay (69.4%, N=34), of propagating cerebral ischemia due to hypoperfusion or other complications (28.6%, N=14), and lack of adequate anesthesia workforce (20.4%, N=7). Conclusions: The most frequent type of anesthesia used by Neurointerventionalists for AIS interventions is GA. Prior to making GA standard of care during AIS intervention, more data are needed about effects on clinical outcomes.